Identification of the Phytochemical Compounds and Their Type I Procollagen Induction in Astragalus membranaceus Sprouts Grown under Different Light Conditions - Seon Young Jeong, Mi Yeon Moon, Eun Kyung Ryu, Je Sung Lee, Joonseok Cha (Journal of Applied Pharmaceutical Science, 2018)
Astragalus membranaceus, a medicinal herb, has been used for diuretic, tonic, anti-viral and antioxidant effects. Its root is widely used in Chinese and Korean traditional medicines, but in this study, the sprout grown optimally in our indoor system was evaluated for cosmetic efficacies. Interestingly, A. membranaceus sprout extract activated the production of type I procollagen by human dermal fibroblast cells in a dose-dependent manner, without showing cell toxicity. A phytochemical study was conducted to identify the active constituents in the extract by solvent fractionation and column purifications. As a result, three compounds: tryptophan (1), linoleic acid (2) and adenine (3) were identified by NMR spectroscopy. Isolated tryptophan was verified to induce the synthesis of the type I procollagen in a dose-dependent manner. These results demonstrate that A. membranaceus sprouts containing tryptophan can be developed as skin care ingredient with the optimization of indoor cultivation system.
Keywords: A. membranaceus sprout, hwanggi, tryptophan, type 1 procollagen.